Li2S4 Anchoring Governs the Catalytic Sulfur Reduction on Defective SmMn2O5 in Lithium–Sulfur Battery. Issue 20 (10th April 2022) - Wang, Li; Hu, Zhonghao; Wan, Xiang; Hua, Wuxing; Li, Huan; Yang, Quan‐Hong; Wang, Weichao
Abstract: The introduction of sulfur redox electrocatalysts has been considered to be an effective strategy to anchor polysulfides on the cathode and reduce the energy barriers of the reactions. Due to the complexity of sulfur redox reactions (SRR/SER), there exist few descriptors to correlate the catalytic performance and the underlying electronic structures of a given catalyst, which inhibits the development of lithium−sulfur catalysts. In this article, upon mullite oxide SmMn2 O5 with various substitutional defects, density functional theory calculations are used to probe the structure–property relationships. It is found that there exists no scaling relationship among the polysulfide binding energies, indicating that the catalytic performance can be tuned by a key intermediate individually. Statistical analysis of various models with different S‐containing intermediates shows that only the Li2 S4 binding energy has a linear correlation with the overpotential, showing the dominant role of Li2 S4 anchoring to determine the catalytic performance. The electronic structure analysis combined with machine learning further quantitatively verifies the coeffect of charge transfer, electronegativity, and work function on the binding strength of the polysulfide Li2 S4 . This work provides a theoretical understanding of the complex SRR/SER mechanisms and sheds light on the rational design of a sulfur redox catalyst. Abstract : Density functional theory calculations for defective mullite SmMn2 O5 show that no scaling relationship exists among the polysulfide binding energies. Instead, a linear correlation is established between the Li2 S4 binding energies and sulfur reduction reaction (SRR) overpotential, shining light onto the design of SRR catalysts based on lattice matching between Li2 S4 and active sites on the catalyst surface.